Compressive strength, microstructure and thermal analysis of autoclaved and air cured structural lightweight concrete made with coal bottom ash and silica fume - Watcharapong Wongkeo (2018)
This research investigated the compressive strength, microstructure and thermal analysis of autoclaved and air cured structural lightweight concrete made with coal bottom ash and silica fume. The results show that bottom ash lightweight concrete autoclaved for 6h gives compressive strength similar to the bottom ash lightweight concrete air cured for 28 days and found that the compressive strength of both bottom ash lightweight concrete increased when silica fume was added to the mix. The highest compressive strength obtained for all mixes was found when coal bottom ash was used at 20% with the addition of silica fume at 5% and that this strength value is significantly higher than that of Portland cement control. The thermal conductivity of all bottom ash lightweight concrete at 28 days and those autoclaved for 6h were found to be slightly higher than that of Portland cement control concrete. Air cued hydration products such as ettringite, calcium silicate hydrate and gehlenite hydrate were detected using thermogravimetric analysis. The tobermorite phase detected in autoclaved bottom ash concrete with silica fume was found to give denser microstructure than the fibrous-like C-S-H phases detected in Portland cement control concrete. © 2010 Elsevier B.V.